A kind of UV adhesive with high bonding performance and preparation method thereof
By using a specific proportion of polyurethane prepolymer, active monomer and photoinitiator in UV glue and adding epoxy resin, the problem of poor bonding strength and adhesion of existing glass adhesive materials is solved, and high bonding performance and rapid curing effect is achieved.
Patent Information
- Application Number
- CN202010215586.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2040-03-25
AI Technical Summary
The existing ordinary glass adhesive materials cannot meet the requirements of rapid curing and easy cleaning, and at the same time there are problems of poor bonding strength and adhesion, making it difficult to achieve a balance between bonding strength and adhesion.
A high-bonding performance UV glue is used, and the preparation raw materials include 15 to 45 parts of polyurethane prepolymer, 60 to 80 parts of active monomer, and 1.5 to 3 parts of photoinitiator. The composition of the UV glue is optimized through the specific ratio of polyol and acrylic monomers, as well as the addition of epoxy resin, to improve its bonding strength and adhesion.
UV glue maintains excellent adhesion and bonding strength on the glass surface, while shortening curing time and improving production efficiency.
Smart Images

Figure BDA0002424293020000141 
Figure BDA0002424293020000142 
Figure BDA0002424293020000151
Abstract
Description
Technical Field
[0001] The present invention relates to the field of ultraviolet curing adhesives, and more specifically, to a high-bonding performance UV adhesive and a preparation method thereof. Background Art
[0002] UV curing adhesive materials are green fine chemical products due to their advantages such as fast curing speed, pollution-free, simple curing equipment, solvent-free, and suitable for automated production. They have the tendency to replace traditional adhesive materials in many application fields. At the same time, their application in the field of glass adhesives is also growing rapidly.
[0003] Glass is a non-stoichiometric compound, generally silicate, and sometimes a mixture of borates or phosphates. Since the surface composition of glass is very different from its bulk composition, the surface energy is high and it is not easy to bond. At present, the existing common glass adhesive materials cannot meet the requirements of fast curing and easy cleaning. Some domestic UV curing adhesive materials have been launched one after another, but a considerable number of products have problems such as poor bonding strength and adhesion. In order to improve the bonding strength of the adhesive material, the adhesion will be reduced accordingly. When the adhesion is improved, the bonding strength will be reduced. Therefore, the bonding strength and adhesion are traded off. The existing products cannot balance the two to achieve high bonding strength and adhesion. Summary of the invention
[0004] In view of some problems existing in the prior art, the first aspect of the present invention provides a high-adhesion performance UV adhesive, wherein the raw materials for preparing the UV adhesive include 15 to 45 parts of a polyurethane prepolymer, 60 to 80 parts of an active monomer, and 1.5 to 3 parts of a photoinitiator, by weight; the raw materials for preparing the polyurethane prepolymer include component A and component B; the component A includes a polyol, an acrylic monomer and an epoxy resin; the component B includes an isocyanate and a catalyst.
[0005] As a preferred technical solution of the present invention, the polyol includes a first component; the relative molecular mass of the first component is 500-1500; the hydroxyl value is 150-250 mgKOH / g, and the viscosity is 200-300 mPa.s.
[0006] As a preferred technical solution of the present invention, the polyol further comprises a second component; the relative molecular mass of the second component is 2500-3500; and the hydroxyl value is 20-40 mgKOH / g.
[0007] As a preferred technical solution of the present invention, the weight ratio of the second component to the first component is 1:(2-4).
[0008] As a preferred technical solution of the present invention, the active monomer includes at least one of ethoxylated nonylphenol acrylate, trimethylolpropane trimethacrylate, polyethylene glycol dimethacrylate, alkoxylated nonylphenol acrylate, benzyl methacrylate, tetrahydrofuran acrylate, lauryl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, polypropylene glycol dimethacrylate, ethoxylated trimethylolpropane trimethacrylate, isooctyl acrylate, dodecyl methacrylate, polyolefin methacrylate, pentaerythritol triallyl ether, dipentaerythritol pentamethacrylate, dipentaerythritol pentaacrylate, isobornyl acrylate, hydroxyalkyl methacrylate, caprolactone methacrylate, hydroxyethyl methacrylate, and hydroxyethyl methacrylate.
[0009] As a preferred technical solution of the present invention, the active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate.
[0010] As a preferred technical solution of the present invention, the weight ratio of hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate is 1: (0.8-1.2): (0.4-0.6): (0.45-0.65).
[0011] As a preferred technical solution of the present invention, the acrylic monomer contains at least one of -OH, -NH-, and -NH2.
[0012] As a preferred technical solution of the present invention, the acrylic monomer includes at least one of hydroxyethyl acrylate, 4-hydroxybutyl acrylate, 3-(dimethylamino)ethyl acrylate, N,N-dimethylaminoethyl acrylate, 2,3-dihydroxypropyl acrylate, 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate, 6-hydroxyhexyl acrylate, and dimethylaminoethyl methacrylate.
[0013] The second aspect of the present invention provides a UV adhesive with high bonding performance for bonding glass.
[0014] Compared with the prior art, the present invention has the following beneficial effects:
[0015] (1) The high-bonding performance UV adhesive provided by the present invention maintains excellent adhesion and bonding strength;
[0016] (2) The high-bonding performance UV glue provided by the present invention has a short curing time, which greatly shortens the production time and improves the production efficiency. DETAILED DESCRIPTION
[0017] The present invention is described below by specific implementation methods, but is not limited to the specific embodiments given below.
[0018] In the first aspect of the present invention, a UV glue with high bonding performance is provided. By weight, the raw materials for its preparation include 15 - 45 parts of polyurethane prepolymer, 60 - 80 parts of reactive monomer, and 1.5 - 3 parts of photoinitiator.
[0019] In one embodiment, by weight, the raw materials for the preparation of the UV glue with high bonding performance further include 0.3 - 0.6 parts of antioxidant, 0.2 - 0.9 parts of thixotropic agent, and 0.1 - 0.8 parts of auxiliary agent.
[0020] In a preferred embodiment, by weight, the raw materials for the preparation of the UV glue with high bonding performance include 30 parts of polyurethane prepolymer, 70 parts of reactive monomer, 2 parts of photoinitiator, 0.45 parts of antioxidant, 0.7 parts of thixotropic agent, and 0.5 parts of auxiliary agent.
[0021] Polyurethane prepolymer
[0022] Polyurethane is a high - molecular polymer formed by the reaction of polyisocyanate and polyether or polyester polyol under certain conditions. The prepolymer of polyurethane is simply a reactive semi - finished product obtained by controlling the reaction ratio of polyisocyanate and polyol. Since there are many types of polyisocyanates and polyols, and the reaction ratios are different.
[0023] In one embodiment, the raw materials for the preparation of the polyurethane prepolymer include component A and component B.
[0024] <Component A>
[0025] In one embodiment, component A includes polyol and acrylic monomer.
[0026] In one embodiment, component A further includes epoxy resin.
[0027] Polyol:
[0028] In one embodiment, the polyol includes the first component.
[0029] Preferably, the polyol further includes the second component.
[0030] In one embodiment, the relative molecular mass of the first component is 500 - 1500; the hydroxyl value is 150 - 250 mgKOH / g, and the viscosity is 200 - 300 mPa·s.
[0031] Preferably, the relative molecular mass of the first component is 700; the hydroxyl value is 238 mgKOH / g; the viscosity is 240 mPa·s.
[0032] The viscosity mentioned in the present invention is the dynamic viscosity, and the test condition is 25°C.
[0033] The first component of the present invention was purchased from Shanghai Kain Chemical Co., Ltd. and the brand name was Dow Polyether Polyol 2070.
[0034] In one embodiment, the relative molecular mass of the second component is 2500-3500; the hydroxyl value is 20-40 mgKOH / g.
[0035] Preferably, the second component comprises at least one of Dynacoll 7210, Dynacoll 7220, Dynacoll 7230, and Dynacoll 7231.
[0036] In one embodiment, the weight ratio of the second component to the first component is 1:(2-4).
[0037] Preferably, the weight ratio of the second component to the first component is 1:3.
[0038] In the process of preparing UV adhesive with high bonding performance, it often happens that when the bonding strength of the obtained UV adhesive is high, the adhesion of the UV adhesive material is low; and when the adhesion of the UV adhesive material is improved, the bonding strength of the UV adhesive material will decrease, and it is difficult to achieve a balance between the two, that is, it is impossible to prepare a UV adhesive material with high bonding strength and adhesion. However, the applicant unexpectedly found that when polyols with different molecular weights are used to prepare the required polyurethane prepolymer, that is, relative molecular weights of 2500-3500, hydroxyl values of 20-40 mgKOH / g and relative molecular weights of 500-1500, hydroxyl values of 150-250 mgKOH / g, and viscosities of 200-300 mPa.s (25 degrees C); especially when the polyols are Dynacoll 7210, Dynacoll 7220, Dynacoll 7230, Dynacoll When any one of 7231 is used together with Dow polyether polyol 2070, the adhesion and bonding strength of the resulting UV adhesive are improved. This may be because the flexible chain segment with a relative molecular mass of 500-1500, together with the polyol with a relative molecular mass of 2500-3500, can form chemical bonds and hydrogen bonds on the glass surface, and at the same time have a certain cohesive force, thereby achieving simultaneous improvement of adhesion and shear strength.
[0039] Acrylic monomers:
[0040] In one embodiment, the acrylic monomer contains at least one of -OH, -NH-, and -NH2.
[0041] Preferably, the acrylic monomer includes at least one of hydroxyethyl acrylate, 4-hydroxybutyl acrylate, 3-(dimethylamino)ethyl acrylate, N,N-dimethylaminoethyl acrylate, 2,3-dihydroxypropyl acrylate, 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate, 6-hydroxyhexyl acrylate, and dimethylaminoethyl methacrylate; further preferably, the acrylic monomer includes at least one of 2,3-dihydroxypropyl acrylate, 2-[2-(2-hydroxyethoxy)ethoxy]ethyl-2-acrylate, and 6-hydroxyhexyl acrylate; more preferably, the acrylic monomer includes 2-[2-(2-hydroxyethoxy)ethoxy]ethyl-2-acrylate.
[0042] The 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate of the present invention has CAS number: 16695-45-7.
[0043] Preferably, the weight ratio of the polyol to the acrylate monomer is 1:(2.5-4.5); more preferably, the weight ratio of the polyol to the acrylate monomer is 1:3.
[0044] Epoxy resin:
[0045] In one embodiment, the epoxy resin includes at least one of 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate, di(2-oxiranylethyl) ether, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexane carbonate, bis-(3,4-epoxycyclohexylmethyl) adipate, hydrogenated bisphenol A epoxy resin, and hydrogenated bisphenol F epoxy resin.
[0046] Preferably, the epoxy resin includes 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl ester and di(2-oxiranylethyl) ether.
[0047] Preferably, the molar ratio of 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate and di(2-oxiranylethyl)ether is 1:(0.2-0.5):(0.8-1.5); more preferably, the molar ratio of 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate and di(2-oxiranylethyl)ether is 1:0.3:1.2.
[0048] The 1,2-epoxy-5-hexene of the present invention has a CAS number of 10353-53-4; the 8-(3-octyloxirane-2-yl)octyl ester has a CAS number of 106-84-3; and the di(2-oxiranylethyl)ether has a CAS number of 10580-77-5.
[0049] Preferably, the weight ratio of the polyol to the epoxy resin is 1:(0.3 - 0.6); more preferably, the weight ratio of the polyol to the epoxy resin is 1:0.45.
[0050] During the use of the UV glue, the applicant unexpectedly found that when using epoxy resin as a raw material in the preparation of polyurethane prepolymer, the bonding strength and adhesion of the UV colloid can be further improved. Especially when using 1,2-epoxy-5-hexene, octyl 8-(3-octyloxiran-2-yl)octanoate, bis(2-oxiranylethyl) ether; and the molar ratio of the three is 1:(0.2 - 0.5):(0.8 - 1.5), this may be due to the combination of mono-epoxy group, bis-epoxy group, long-chain epoxy and short-chain epoxy to achieve the modification of epoxy at the molecular level, which is beneficial to reducing the system viscosity, forming an appropriate crosslinking density during the curing process, reducing the volume shrinkage rate during curing, improving the spreading of the colloid on the glass surface, increasing the interaction between the colloid and the glass, and further optimizing the bonding strength and adhesion.
[0051] <Component B>
[0052] In one embodiment, the Component B includes isocyanate and a catalyst.
[0053] Preferably, the weight ratio of the Component A to the Component B is 1:(1 - 6); more preferably, the weight ratio of the Component A to the Component B is 1:3.
[0054] Preferably, the weight portion of the catalyst is 0.3 - 3 parts; more preferably, the weight portion of the catalyst is 2 parts.
[0055] In one embodiment, the isocyanate is diisocyanate.
[0056] Preferably, the diisocyanate includes at least one of phenyl diisocyanate, 4,4-diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, toluene 2,4-diisocyanate, and benzylidene diisocyanate; more preferably, the diisocyanate includes toluene 2,4-diisocyanate.
[0057] In one embodiment, the catalyst includes at least one of N,N-dimethylcyclohexylamine, N-ethylmorpholine, N-methylmorpholine, N,N-diethylpiperazine, triethanolamine, DMEA, T-9, and T-12.
[0058] Preferably, the catalyst includes triethanolamine.
[0059] In one embodiment, the preparation method of the polyurethane prepolymer includes: adding component A into a four-necked flask, vacuum dehydrating at 100-110°C, cooling to 55-70°C; adding component B, heating to 75°C, continuing to keep warm, and after the reaction is complete, discharging the material to obtain the prepolymer.
[0060] In one embodiment, the preparation method of the polyurethane prepolymer includes: adding component A into a four-necked flask, vacuum dehydrating at 105°C, cooling to 65°C; adding component B, heating to 75°C, continuing to keep warm, and after the reaction is complete, discharging the material to obtain the prepolymer.
[0061] Active monomer
[0062] In one embodiment, the active monomer includes at least one of ethoxylated nonylphenol acrylate, trimethylolpropane trimethacrylate, polyethylene glycol dimethacrylate, alkoxylated nonylphenol acrylate, benzyl methacrylate, tetrahydrofuran acrylate, lauryl acrylate, 2-phenoxyethyl acrylate, isodecyl acrylate, polypropylene glycol dimethacrylate, ethoxylated trimethylolpropane trimethacrylate, isooctyl acrylate, dodecyl methacrylate, polyolefin methacrylate, pentaerythritol triallyl ether, dipentaerythritol pentamethacrylate, dipentaerythritol pentaacrylate, isobornyl acrylate, hydroxyalkyl methacrylate, caprolactone methacrylate, hydroxyethyl methacrylate, and hydroxyethyl methacrylate.
[0063] Preferably, the active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate.
[0064] Preferably, the weight ratio of hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate is 1:(0.8-1.2):(0.4-0.6):(0.45-0.65); more preferably, the weight ratio of hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate is 1:1:0.55:0.5.
[0065] In UV adhesive systems, active monomers are generally required to participate in the curing process of UV adhesives. However, large shrinkage stress often occurs during the curing process, resulting in poor adhesion of the final colloid. The applicant unexpectedly discovered during the experiment that when hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate, and isobornyl acrylate are used together as active monomers, the adhesion of the cured colloid material is better, especially when the weight ratio of hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate, and isobornyl acrylate is 1: (0.8-1.2): (0.4-0.6): (0.45-0.65), not only the adhesion is improved, but also the time required for the curing process is reduced. This may be due to the combined effect of short and long chains and side chain structures of different ring structures to reduce volume shrinkage during the curing process, while reducing the crosslinking density of the adhesive layer during the curing process, thereby improving its adhesion to the glass. In addition, because it works together with different types of polyols with a certain hydroxyl value, it promotes the curing process, thereby shortening the curing time.
[0066] Photoinitiator
[0067] Photoinitiator, also known as photosensitizer or photocuring agent, is a type of compound that can absorb energy of a certain wavelength in the ultraviolet light region (250-420nm) or visible light region (400-800nm) to produce free radicals, cations, etc., thereby initiating monomer polymerization, cross-linking and curing.
[0068] In one embodiment, the photoinitiator includes at least one of Irgacure 184, Darocure 1173, Irgacure 819, Irgacure 907, and TPO.
[0069] Preferably, the photoinitiator is Irgacure 819, CAS: 162881-26-7.
[0070] The Irgacure 184 CAS: 947-19-3; Darocure 1173 CAS: 7473-98-5; Irgacure 819 CAS: 162881-26-7; Irgacure 907 CAS: 71868-10-5; and TPO CAS: 75980-60-8 described in the present invention.
[0071] Antioxidants
[0072] In one embodiment, the antioxidant includes at least one of butylated hydroxyanisole, butylated hydroxytoluene, propyl gallate, tert-butylhydroquinone, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate, tris[2,4-di-tert-butylphenyl]phosphite, antioxidant 626, and 2,2'-thiobis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
[0073] The present invention does not impose any particular limitation on the antioxidant.
[0074] Thixotropic agent
[0075] In one embodiment, the thixotropic agent includes at least one of fumed silica, precipitated white carbon black, hydrogenated castor oil, organic bentonite, fine particle alumina, flaky alumina, layered compounds, and needle-shaped compounds.
[0076] Preferably, the thixotropic agent comprises fumed silica.
[0077] The fumed silica described in the present invention was purchased from Hubei Xinrunde Chemical Co., Ltd., 400 mesh.
[0078] Additives
[0079] In one embodiment, the auxiliary agent includes at least one of a storage stabilizer, a filler, a slip agent, a defoamer, and a leveling agent.
[0080] Storage stabilizers include, but are not limited to, hindered phenol antioxidants, diaryl secondary amine antioxidants, hindered amine antioxidants, benzotriazole antioxidants, and phosphite antioxidants.
[0081] Fillers include, but are not limited to, calcium carbonate, silicon dioxide, titanium dioxide, talc, kaolin, bentonite, diatomaceous earth, aluminum oxide, zinc oxide, iron oxide, magnesium oxide, tin oxide, titanium oxide, magnesium hydroxide, aluminum hydroxide, magnesium carbonate, barium sulfate, and gypsum.
[0082] The slip agent includes, but is not limited to, liquid paraffin, petrolatum, synthetic paraffin, polyethylene wax, and polypropylene wax.
[0083] Defoaming agents include but are not limited to BYK-071, BYK-060N, BYK-067, BYK-088, BYK-051, BYK-052, BYK-053, BYK-A550, B YK-A560, BYK-057, BYK-077, BYK-354, BYK-020, BYK-322, BYK-320, BYK-359, BYK-065, TEGO Airex 920, TEGO Airex 910, TEGO Airex 900, TEGO Airex 962, TEGO Airex 931, TEGO Airex 986, TEGO Rad 2500, TEGO Airex 910, TEGO Foamex 810.
[0084] Leveling agents include, but are not limited to, polyvinyl butyral, polyacrylate, polyether-modified polydimethylsiloxane copolymer, and polysiloxane-polyether copolymer.
[0085] In one embodiment, the preparation method of the high-adhesion UV glue includes: adding the raw materials for preparing the high-adhesion UV glue except the photoinitiator into a mixer, stirring thoroughly to obtain a mixture, then adding the photoinitiator to cause a curing reaction, touching the surface of the adhesive layer lightly with a finger, if it feels a little sticky but there is no glue on the finger, stop the reaction, and vacuumize and completely degas to obtain the mixture; the conditions for the curing reaction are: irradiation with a 250W ultraviolet lamp, and the lamp distance is 4cm.
[0086] The second aspect of the present invention provides a UV adhesive with high bonding performance for bonding glass.
[0087] Example
[0088] Hereinafter, the present invention is described in more detail by examples, but it should be understood that these examples are merely illustrative and non-restrictive. If there is no other explanation, the raw materials used in the following examples are all commercially available.
[0089] Example 1
[0090] Embodiment 1 of the present invention provides a UV adhesive with high bonding performance. The raw materials for its preparation include, by weight, 15 parts of polyurethane prepolymer, 60 parts of active monomer, 1.5 parts of photoinitiator, 0.3 parts of antioxidant, 0.2 parts of thixotropic agent, and 0.1 parts of auxiliary agent.
[0091] The polyurethane prepolymer includes component A and component B; component A includes polyol, acrylic monomer, epoxy resin; the weight ratio of the polyol to the acrylic monomer is 1:2.5; the weight ratio of the polyol to the epoxy resin is 1:0.3; the polyol includes a second component and a first component, and the weight ratio is 1:2; the first component is purchased from Shanghai Kain Chemical Co., Ltd., and the brand is Dow Polyether Polyol 2070; the second component is Dynacoll 7210, purchased from Shanghai Kain Chemical Co., Ltd.; the acrylic monomer is 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate; the epoxy resin includes 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate and di(2-oxiranylethyl) ether, and the molar ratio thereof is 1:0.2:0.8; the B component includes isocyanate and 0.3 parts by weight of catalyst, and the weight ratio of the A component to the B component is 1:1; the diisocyanate is toluene 2,4-diisocyanate; and the catalyst includes triethanolamine.
[0092] The preparation method of the polyurethane prepolymer comprises: putting component A into a four-necked flask, vacuum dehydrating at 105° C., cooling to 65° C.; adding component B, heating to 75° C., continuing to keep the temperature, and discharging the material after the reaction is complete.
[0093] The active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate, and the weight ratio thereof is 1:0.8:0.4:0.45; the photoinitiator is Irgacure819; the antioxidant is tert-butylhydroquinone; the thixotropic agent is fumed silica, purchased from Hubei Xinrunde Chemical Co., Ltd., 400 mesh; the auxiliary agent is a defoamer, and the defoamer is BYK-071.
[0094] The preparation method of the high-bonding performance UV glue comprises: adding the raw materials for preparing the high-bonding performance UV glue except the photoinitiator into a mixer, fully stirring to obtain a mixture, then adding the photoinitiator to cause a curing reaction, lightly touching the surface of the adhesive layer with a finger, if it feels a little sticky but there is no glue on the finger, the reaction is stopped, and vacuuming is performed to completely degas. The curing reaction is obtained under the following conditions: irradiation with a 250W ultraviolet lamp and a lamp distance of 4cm.
[0095] The high bonding performance UV glue is used for bonding glass.
[0096] Example 2
[0097] Embodiment 2 of the present invention provides a high-adhesive performance UV adhesive, and its preparation raw materials include 45 parts of polyurethane prepolymer, 80 parts of active monomer, 3 parts of photoinitiator, 0.6 parts of antioxidant, 0.9 parts of thixotropic agent, and 0.8 parts of auxiliary agent by weight.
[0098] The polyurethane prepolymer includes component A and component B; component A includes polyol, acrylic monomer, epoxy resin; the weight ratio of the polyol to the acrylic monomer is 1:4.5; the weight ratio of the polyol to the epoxy resin is 1:0.6; the polyol includes a second component and a first component, and the weight ratio is 1:4; the first component is purchased from Shanghai Kain Chemical Co., Ltd., and the brand is Dow Polyether Polyol 2070; the second component is Dynacoll 7220, purchased from Shanghai Kain Chemical Co., Ltd.; the acrylic monomer is 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate; the epoxy resin includes 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate and di(2-oxiranylethyl) ether, and the molar ratio thereof is 1:0.5:1.5; the B component includes isocyanate and 3 parts by weight of catalyst, and the weight ratio of the A component to the B component is 1:6; the diisocyanate is toluene 2,4-diisocyanate; and the catalyst includes triethanolamine.
[0099] The preparation method of the polyurethane prepolymer comprises: putting component A into a four-necked flask, vacuum dehydrating at 105° C., cooling to 65° C.; adding component B, heating to 75° C., continuing to keep the temperature, and discharging the material after the reaction is complete.
[0100] The active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate, and the weight ratio thereof is 1:1.2:0.6:0.65; the photoinitiator is Irgacure819; the antioxidant is tert-butylhydroquinone; the thixotropic agent is fumed silica, purchased from Hubei Xinrunde Chemical Co., Ltd., 400 mesh; the auxiliary agent is a defoamer, and the defoamer is BYK-071.
[0101] The preparation method of the high-bonding performance UV glue comprises: adding the raw materials for preparing the high-bonding performance UV glue except the photoinitiator into a mixer, fully stirring to obtain a mixture, then adding the photoinitiator to cause a curing reaction, lightly touching the surface of the adhesive layer with a finger, if it feels a little sticky but there is no glue on the finger, the reaction is stopped, and vacuuming is performed to completely degas. The curing reaction is obtained under the following conditions: irradiation with a 250W ultraviolet lamp and a lamp distance of 4cm.
[0102] The high bonding performance UV glue is used for bonding glass.
[0103] Example 3
[0104] Embodiment 3 of the present invention provides a high-adhesive performance UV adhesive, and its preparation raw materials include 30 parts of polyurethane prepolymer, 70 parts of active monomer, 2 parts of photoinitiator, 0.45 parts of antioxidant, 0.7 parts of thixotropic agent, and 0.5 parts of auxiliary agent by weight.
[0105] The polyurethane prepolymer includes component A and component B; component A includes polyol, acrylic monomer, epoxy resin; the weight ratio of the polyol to the acrylic monomer is 1:3; the weight ratio of the polyol to the epoxy resin is 1:0.45; the polyol includes a second component and a first component, and the weight ratio is 1:3; the first component is purchased from Shanghai Kain Chemical Co., Ltd., and the brand is Dow Polyether Polyol 2070; the second component is Dynacoll 7230, purchased from Shanghai Kain Chemical Co., Ltd.; the acrylic monomer is 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate; the epoxy resin includes 1,2-epoxy-5-hexene, 8-(3-octyloxirane-2-yl)octyl octanoate and di(2-oxiranylethyl) ether, and the molar ratio thereof is 1:0.3:1.2; the B component includes isocyanate and 2 parts by weight of catalyst, and the weight ratio of the A component to the B component is 1:3; the diisocyanate is toluene 2,4-diisocyanate; and the catalyst includes triethanolamine.
[0106] The preparation method of the polyurethane prepolymer comprises: putting component A into a four-necked flask, vacuum dehydrating at 105° C., cooling to 65° C.; adding component B, heating to 75° C., continuing to keep the temperature, and discharging the material after the reaction is complete.
[0107] The active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate, and the weight ratio thereof is 1:1:0.55:0.5; the photoinitiator is Irgacure819; the antioxidant is tert-butylhydroquinone; the thixotropic agent is fumed silica, purchased from Hubei Xinrunde Chemical Co., Ltd., 400 mesh; the auxiliary agent is a defoamer, and the defoamer is BYK-071.
[0108] The preparation method of the high-bonding performance UV glue comprises: adding the raw materials for preparing the high-bonding performance UV glue except the photoinitiator into a mixer, fully stirring to obtain a mixture, then adding the photoinitiator to cause a curing reaction, lightly touching the surface of the adhesive layer with a finger, if it feels a little sticky but there is no glue on the finger, the reaction is stopped, and vacuuming is performed to completely degas. The curing reaction is obtained under the following conditions: irradiation with a 250W ultraviolet lamp and a lamp distance of 4cm.
[0109] The high bonding performance UV glue is used for bonding glass.
[0110] Example 4
[0111] Embodiment 4 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation is the same as that of Embodiment 3, except that the component A includes a polyol and an acrylic monomer.
[0112] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0113] The high bonding performance UV glue is used for bonding glass.
[0114] Example 5
[0115] Example 5 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the epoxy resin is 1,2-epoxy-5-hexene and 8-(3-octyloxirane-2-yl)octyl octanoate, and the molar ratio thereof is 1:0.3.
[0116] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0117] The high bonding performance UV glue is used for bonding glass.
[0118] Example 6
[0119] Example 6 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the epoxy resin is 1,2-epoxy-5-hexene and di(2-oxiranylethyl) ether, and the molar ratio thereof is 1:1.2.
[0120] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0121] The high bonding performance UV glue is used for bonding glass.
[0122] Example 7
[0123] Example 7 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the epoxy resin is 8-(3-octyloxirane-2-yl)octyl ester and di(2-oxiranylethyl) ether, and the molar ratio thereof is 0.3:1.2.
[0124] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0125] The high bonding performance UV glue is used for bonding glass.
[0126] Example 8
[0127] Example 8 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the polyol includes a first component.
[0128] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0129] The high bonding performance UV glue is used for bonding glass.
[0130] Example 9
[0131] Example 9 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation is the same as that of Example 3, except that the polyol includes a second component.
[0132] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0133] The high bonding performance UV glue is used for bonding glass.
[0134] Example 10
[0135] Example 10 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation is the same as that of Example 3, except that the second component is Dynacoll 7250 purchased from Shanghai Kain Chemical Co., Ltd.
[0136] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0137] The high bonding performance UV glue is used for bonding glass.
[0138] Embodiment 11
[0139] Example 11 of the present invention provides a high-bonding performance UV adhesive, and its specific implementation method is the same as that of Example 3, except that the first component is purchased from Shanghai Kain Chemical Co., Ltd. and the brand is Dow polyether polyol CP450.
[0140] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0141] The high bonding performance UV glue is used for bonding glass.
[0142] Example 12
[0143] Example 12 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the active monomers are hydroxyethyl methacrylate and benzyl methacrylate, and the weight ratio thereof is 1:1.
[0144] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0145] The high bonding performance UV glue is used for bonding glass.
[0146] Example 13
[0147] Example 13 of the present invention provides a UV adhesive with high bonding performance, and its specific implementation method is the same as that of Example 3, except that the active monomers are benzyl methacrylate, lauryl acrylate, and isobornyl acrylate; and their weight ratio is 1:0.55:0.5.
[0148] The specific implementation methods of the polyurethane preparation method and the high-bonding performance UV adhesive preparation method are the same as those in Example 3.
[0149] The high bonding performance UV glue is used for bonding glass.
[0150] Performance Evaluation
[0151] 1. Adhesion test: The adhesion of the high-bonding performance UV adhesive obtained in Examples 1 to 13 to glass was tested according to the coating film test method of GB / T9286-88.
[0152] 2. Tensile shear strength test: The tensile shear strength of the glass bonded with the high bonding performance UV adhesive obtained in Examples 1 to 11 was tested according to GB / T7124-2008 standard.
[0153] 3. Curing time: The curing time of the high-adhesive UV adhesive obtained in Examples 1 to 3 and 12 to 13 was tested by the finger touch method. If the adhesive layer surface is slightly sticky but no adhesive is on the finger, the surface is considered dry (refer to GB 1728-79 Determination of drying time of paint film and putty film). Experimental conditions: A portable UV curing machine provides 250W ultraviolet light irradiation, the lamp distance is 4cm, and the measurement unit is s.
[0154] Table 1
[0155] Adhesion(grade) Example 1 0 Example 2 0 Example 3 0 Example 4 2 Example 5 1 Example 6 1 Example 7 1 Example 8 2 Example 9 3 Example 10 2 Embodiment 11 1 Example 12 2 Example 13 3
[0156] Table 2
[0157]
[0158] Table 3
[0159]
[0160]
[0161] From the test results of Table 1, Table 2 and Table 3, it can be seen that the high bonding performance UV glue provided by the present invention has excellent adhesion to glass, while maintaining excellent bonding performance and short curing time, which greatly shortens the production time and improves production efficiency.
[0162] The foregoing examples are merely illustrative and are used to explain some features of the method of the present invention. The appended claims are intended to claim the widest possible range that can be conceived, and the embodiments presented herein are only illustrations of selected implementations according to the combination of all possible embodiments. Therefore, it is the applicant's intention that the appended claims are not limited by the selection of examples that illustrate the features of the present invention. Some numerical ranges used in the claims also include sub-ranges within them, and changes in these ranges should also be interpreted as being covered by the appended claims where possible.
Claims
1. A high bonding performance UV adhesive, characterized in that: The raw materials for preparing the polyurethane prepolymer include 15 to 45 parts by weight, 60 to 80 parts by weight of active monomers, and 1.5 to 3 parts by weight of photoinitiator; the raw materials for preparing the polyurethane prepolymer include component A and component B; the component A includes polyol, acrylic monomer and epoxy resin; the component B includes isocyanate and a catalyst; The polyol comprises a first component; the first component is Dow polyether polyol 2070; The polyol further comprises a second component; the second component comprises at least one of Dynacoll 7210, Dynacoll 7220, Dynacoll 7230, and Dynacoll 7231; The active monomers include hydroxyethyl methacrylate, benzyl methacrylate, lauryl acrylate and isobornyl acrylate in a weight ratio of 1: (0.8-1.2): (0.4-0.6): (0.45-0.65); The epoxy resins are 8-(3-octyloxirane-2-yl)octyl ester and di(2-oxiranylethyl) ether.
2. The high bonding performance UV adhesive according to claim 1, characterized in that: The weight ratio of the second component to the first component is 1:(2-4).
3. The high bonding performance UV adhesive according to any one of claims 1 to 2, characterized in that: The acrylic monomer contains at least one of -OH, -NH-, and -NH2.
4. The high bonding performance UV adhesive according to claim 3, characterized in that: The acrylic monomer includes at least one of hydroxyethyl acrylate, 4-hydroxybutyl acrylate, 3-(dimethylamino)ethyl acrylate, N,N-dimethylaminoethyl acrylate, 2,3-dihydroxypropyl acrylate, 2-[2-(2-hydroxyethoxy)ethoxy]ethyl 2-acrylate, 6-hydroxyhexyl acrylate, and dimethylaminoethyl methacrylate.
5. A UV adhesive with high bonding performance according to any one of claims 1 to 4 for bonding glass.
Citation Information
Patent Citations
Single-component low-viscosity potting adhesive, and preparation method and application thereof
CN102816550A